(untitled) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2022)
This research aims aimed tounderstand the effect of job stress and job satisfaction on the performance of SMA Negeri 1 Pundong teachers. This research uses a quantitative approach. The sample in this study was the entire population of SMA Negeri 1 Pundong teachers, amounting to 40 teachers. Collecting data using a questionnaire. The data analysis technique used in this study is multiple regression analysis using SPSS version 25 software. The results of this study indicate that work stress and job satisfaction together have a significant effect on teacher performance as indicated by f count (24.833) greather than f table (3.25) with a significance level of 0.000 less than0.05. Similarly, the T test (Partial) for the variable job satisfaction (X2) has a positive and significant effect on teacher performance, the value of t count (5,146) greather than t table (2,026) with a significance level of 0.000 less than 0.05, but there is a work stress variable (X1) which has no negative and significant effect on teacher performance, the value of t count (1.995) less than t table (2.026) with a significance level of 0.053 greather than 0.05. While the magnitude of the relationship between work stress and job satisfaction on teachers obtained an R2 value of 0.573 or 57.3% while the remaining 42.7% was influenced by other variables not included in this study.